2016
DOI: 10.1371/journal.pone.0160950
|View full text |Cite
|
Sign up to set email alerts
|

Noise Enhances Action Potential Generation in Mouse Sensory Neurons via Stochastic Resonance

Abstract: Noise can enhance perception of tactile and proprioceptive stimuli by stochastic resonance processes. However, the mechanisms underlying this general phenomenon remain to be characterized. Here we studied how externally applied noise influences action potential firing in mouse primary sensory neurons of dorsal root ganglia, modelling a basic process in sensory perception. Since noisy mechanical stimuli may cause stochastic fluctuations in receptor potential, we examined the effects of sub-threshold depolarizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 37 publications
0
20
0
1
Order By: Relevance
“…Although the underlying neural mechanisms are not completely understood [ 19 ], single unit recordings in visual cortex have revealed an increase in the SNR of neuronal spiking when an optimal level of noise is applied to a visual stimulus [ 20 ], consistent with a stochastic resonance mechanism. This is likely due to the recruitment of voltage-gated sodium channels by the noise [ 21 23 ]. Our previous study [ 18 ], together with several related investigations [ 24 , 25 ], point to stochastic resonance as an underlying mechanism by which non-invasive brain stimulation can enhance behavioural performance when it is applied concurrently during task performance.…”
Section: Introductionmentioning
confidence: 99%
“…Although the underlying neural mechanisms are not completely understood [ 19 ], single unit recordings in visual cortex have revealed an increase in the SNR of neuronal spiking when an optimal level of noise is applied to a visual stimulus [ 20 ], consistent with a stochastic resonance mechanism. This is likely due to the recruitment of voltage-gated sodium channels by the noise [ 21 23 ]. Our previous study [ 18 ], together with several related investigations [ 24 , 25 ], point to stochastic resonance as an underlying mechanism by which non-invasive brain stimulation can enhance behavioural performance when it is applied concurrently during task performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, single unit recordings have shown that sensory neurons in the visual cortex are sensitive to a stochastic resonance mechanism, e.g., there is an increase in the SNR of the firing rate of neurons when an optimal level of noise is applied to a visual stimulus [44]. This is likely due to the recruitment of voltage-gated sodium channels by the noise [45-47].…”
Section: Discussionmentioning
confidence: 99%
“…100 V/m; Roth et al 1991Roth et al , 2007. By contrast, detrimental effects of noise on signal detection demonstrated in vitro, usually requires noise amplitudes which are in the same order or larger than the activation stimulus (see for example Onorato et al 2016).…”
Section: Acute Trns-induced Noise Benefits Are Partly Consistent Withmentioning
confidence: 99%
“…Even though the neurophysiological mechanism of tRNS is not completely understood, it has been demonstrated that electrical random noise increases action potential firing in primary sensory neurons of dorsal root ganglia (Onorato et al 2016). The authors suggested that such enhancement occurred by the concurrent activation of voltage-gated sodium channels mediated by the SR phenomenon.…”
Section: What Is the Possible Neurophysiological Substrate Mediating mentioning
confidence: 99%
See 1 more Smart Citation